2021
DOI: 10.1016/j.jds.2020.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Glycated hemoglobin influence on periodontal status, pathogens and salivary interleukins in type II diabetic Tunisian subjects with chronic periodontitis

Abstract: Background/purpose Studies have shown that there is a possible correlation between the amount of glycated hemoglobin and the periodontal status. The goal of this study was to investigate the relationship between glycated hemoglobin (HbA1c) and the prevalence of gingival pathogens and circulating interleukin levels in type II diabetic Tunisian subjects. Material and methods The research included four groups; 30 healthy subjects (H group), 30 non-diabetic subjects sufferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The recent studies in DM patients also revealed a decrease in HbA1c after a periodontal treatment. 40 However, in contrast to the ndings of Cintra et al 41 , they demonstrated that the increase of HbA1c is regardless of the presence of AP and/or periodontal disease. As in our study, no statistically insigni cant obtained between the groups in short-term is somewhat due to the reason that periapical healing is sometimes slow and nal results may not be possible to assess in a short time.…”
Section: Discussionmentioning
confidence: 74%
“…The recent studies in DM patients also revealed a decrease in HbA1c after a periodontal treatment. 40 However, in contrast to the ndings of Cintra et al 41 , they demonstrated that the increase of HbA1c is regardless of the presence of AP and/or periodontal disease. As in our study, no statistically insigni cant obtained between the groups in short-term is somewhat due to the reason that periapical healing is sometimes slow and nal results may not be possible to assess in a short time.…”
Section: Discussionmentioning
confidence: 74%
“…Table 1 summarizes the characteristics of the studies reviewed based on the year of publication. The USA 34 , 43 , 44 conducted three of the articles, with one each from India, 35 Iran, 36 China (two articles), 37 , 38 Egypt, 39 Tunisia, 41 and Brazil (two articles). 40 , 42 The research participant count in each article ranges from 15 to 248 diabetic patients, resulting in a total of 801 diabetic patients, both with and without oral diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows that the studies were conducted in type 2 diabetes populations in the USA, 34 , 43 , 44 India, 35 Iran, 36 China, 37 , 38 Egypt, 39 Brazil, 40 , 42 and Tunisia. 41 The most observed DM-related oral diseases were periodontitis, with 10 articles, and one article discussed oral candidiasis. Samples taken to check IL-10 were generally from blood, saliva, gingival crevicular fluid (GCF), and gingival tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were immediately put on ice and then transferred to the laboratory. After sampling, aliquots were prepared, and the samples were frozen at−80 C until an analysis was carried out [ 13 ].…”
Section: Study Investigationsmentioning
confidence: 99%